Torsional Vibrations at Guide-Vane Shaft of Pump–Turbine Model - Andrej Predin (Shock and Vibration)
This article focuses on the problem of guide-vane vibrations of reversible pump–turbines, especially, in the pump mode. These vibrations are transmitted to the guide-vane shaft torque. The guide-vane vibrations are caused by the impeller exit flow, which has a turbulent and partly nondeterministic property. Experimentally determined flow velocities at the impeller exit are given. The mathematical models for theoretical torsional vibration prediction formulated using linear and nonlinear differential equations are presented. The results of theoretical calculations are compared with measurement results. The possibility of transferring the parameters from the model to the prototype is discussed.